2021
DOI: 10.1002/saj2.20206
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinity gradients in grasslands alter soil bacterial community composition and function

Abstract: Clarifying the bacterial community composition and function in alkali soils is pivotal to the soil capability of sustaining venerable ecosystems. Using MiSeq sequencing, PICRUSt, and Biolog (https://www.biolog.com), we investigated the bacterial community composition and metabolic function of microbes in three soils differing in the severity of alkalinity. A high level of alkalinity deceased the diversity of microbial community and altered microbial community composition with the increase in relative abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Poor physical structure, nutrient de ciency, and high basic salinity of mud at soil inhibit the activity of soil bacteria and affect the diversity of bacterial communities (Zhao et al, 2022;Albdaiwi et al, 2019). Soil bacteria participate in the ecological process of material decomposition and nutrient cycling, and their metabolic activities play an important role in promoting the mineralization of organic matter and the formation of humus in mud at soil, which is one of the main factors to restore and maintain the productivity of saline alkali soil (Xiang et al, 2021; Bridgett and van der Putten, 2014). So, bacterial communities determine the sustainable productivity of the mud at agricultural ecosystem to a large extent (Bender et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor physical structure, nutrient de ciency, and high basic salinity of mud at soil inhibit the activity of soil bacteria and affect the diversity of bacterial communities (Zhao et al, 2022;Albdaiwi et al, 2019). Soil bacteria participate in the ecological process of material decomposition and nutrient cycling, and their metabolic activities play an important role in promoting the mineralization of organic matter and the formation of humus in mud at soil, which is one of the main factors to restore and maintain the productivity of saline alkali soil (Xiang et al, 2021; Bridgett and van der Putten, 2014). So, bacterial communities determine the sustainable productivity of the mud at agricultural ecosystem to a large extent (Bender et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2018). The highest relative abundance of Proteobacteria in CCM treatment may be due to the fact that the increased level of soil humus caused by the application of fermented cow manure positively affected the increase in the number of Proteobacteria, a group of eutrophic bacteria, and resulted in a relative decrease in the proportion of nutrient-poor bacteria in the soil(Liu et al, 2021). Moreover, a large number of Proteobacteria contributed to soil carbon storage through the synthesis of microbial mucilage and polysaccharides that contribute to the stabilization of aggregates in mud at soils(Pascual et al, 2018).…”
mentioning
confidence: 99%
“…In a study by Sun et al (2021) on the abundance and vertical distribution of soil microbiomes in coastal saline soils under different amelioration measures, it was similarly found that soil bacteria had a more pronounced response to salt concentration, with significantly higher abundance than fungi and archaea. In addition, soil bacteria are involved in the ecological processes of material decomposition and nutrient cycling, and their metabolic activities play an important role in promoting the mineralization of organic matter and humus formation in mudflat soils, which is one of the main factors in restoring and maintaining the productivity of saline soils (Bardgett and van der Putten, 2014;Xiang et al, 2021), so bacterial communities are to a large extent determines the sustainable productivity of beach agroecosystems (Bender et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the characteristics of soil bacterial community structure along an elevation gradient on a mountainside in northwest Sichuan were explored using high-throughput sequencing technology, and the responses of soil bacterial communities to climate change were further studied by reciprocal soil translocation at three elevations with 1000 m interval. In addition, the function of soil microorganisms is closely related to microbial community composition 26 , 27 , and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) analysis can reliably predict the metabolic functions of soil bacterial communities 28 . Therefore, the PICRUSt method was used to predict bacterial community functions according to 16S rRNA sequencing data.…”
Section: Introductionmentioning
confidence: 99%